Age at birth of first child and coronary heart disease risk factors at age 53 years in men and women: British birth cohort study. Issue 2 (9th September 2008) - Hardy, R; Lawlor, D A; Black, S; Mishra, G D; Kuh, D
Abstract : Objective: To assess the associations between parental age at birth of first child and coronary heart disease (CHD) risk factors in men and women. To investigate whether the associations are explained by childhood predictors of age at parenthood or adult lifestyle factors related to child rearing. Methods: Data from 2540 men and women, with CHD risk factors measured at age 53 years, from a birth cohort study of individuals born in Britain in 1946 (Medical Research Council National Survey of Health and Development) and followed up regularly throughout life, were analysed. Results: Younger age at birth of first child in both men and women was associated with poorer mean body mass index (BMI), waist–hip ratio, blood pressure (BP), high-density lipoprotein cholesterol, triglyceride and glycated haemoglobin levels. Mean BMI decreased from 28.0 kg/m 2 (95% CI 27.2 to 28.8) in the teenage motherhood group to 26.8 kg/m 2 (25.9 to 27.7) in the oldest motherhood group (⩾30 years). For men, the equivalent mean values were 28.5 kg/m 2 (27.3 to 29.8) and 27.1 kg/m 2 (26.7 to 27.6). Associations with adiposity, lipid measures and glycated haemoglobin were largely explained by childhood antecedents and adult social and lifestyle variables. Associations with BP remained robust to adjustment: systolic blood pressure remained highest in teenage parents (7.5 mmHg (1.0 to 13.9) difference in women and 8.6 mmHg (0.4 to 16.8) difference in men between the youngest and the oldest parenthood groups) Conclusions: Lifestyle factors, rather than the biological impact of pregnancy, explain the relationship between age at motherhood and CHD risk factors. Family-based lifestyle interventions targeted at young parents may improve their future CHD risk.